Method for producing optical thin film and optical member

By depositing the film in an oxidative atmosphere and contacting the acid solution, the problems of foreign substances and metal impurities in the sol-gel method are solved, and an optical film with high mittance and low refractive index are achieved.

JP2025052653APending Publication Date: 2025-04-07NICHIA CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023161470
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-25
Publication Date
2025-04-07

AI Technical Summary

Technical Problem

When manufacturing antireflective films or optical films, the sol-gel method easily mixes in foreign substances, resulting in a decrease in light transmission mittance and metal deposits may exist on the surface of the film.

Method used

The material is formed by deposition of the film by evaporation in an oxidative atmosphere, and then contacting the deposited film with an acidic solution, and the metal impurities on the surface of the film are removed by acidic environment and ultrasonic vibration to form a thin film structure with a hollow.

Benefits of technology

It effectively reduces the amount of metal present on the film surface, improves light transmission, and forms a film structure with a low refractive index, enhancing the anti-reflection effect on oblique light.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025052653000001_ABST
    Figure 2025052653000001_ABST
Patent Text Reader

Abstract

To provide a method for producing an optical thin film and an optical member.SOLUTION: A method for producing an optical thin film comprises: depositing a thin-film forming material on a deposition target by the vapor deposition technique under a non-oxidizing atmosphere to form a vapor-deposited film; bringing the vapor-deposited film into contact with a first acidic solution containing an acidic substance and having a pH in the range of 2.5 or more and 3.5 or less, to form a porous thin film; and bringing the resulting thin film into contact with a second acidic solution containing an acidic substance and having a pH of 2.0 or less under application of ultrasonic vibration, to dissolve a metal adhering to the surface of the thin film.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for producing an optical thin film and an optical member. [Background technology]

[0002] The lens surfaces of cameras and telescopes are coated with a thin film to reduce reflected light. When attempting to obtain a reflected light reduction effect with a single-layer film, it is effective to form an optical thin film having a refractive index close to the square root of the refractive index of the object to be coated on the outermost surface of the object to be coated. When obtaining an anti-reflection effect for a wide range of wavelengths, it is necessary to form a multi-layer film. Even with such a multi-layer film, an optical thin film having a refractive index lower than the square root of the object to be coated is required to enhance the anti-reflection effect for obliquely incident light.

[0003] In order to obtain a thin film with a refractive index lower than the square root of the area on which it is formed, it is useful to include voids with a refractive index of 1.0 or more within the thin film, and optical thin films containing air have been proposed using a variety of methods, including the sol-gel method. For example, Patent Document 1 describes an antireflection coating including, in order from the glass substrate side, a first phase mainly composed of aluminum oxide formed by a vacuum deposition method, a second layer made of at least one material selected from the group consisting of MgF2 and SiO2 formed by a vacuum deposition method, and a third layer made of an aggregate of mesoporous silica nanoparticles on the second layer. Furthermore, Patent Document 2 describes an antireflection coating comprising, on a substrate, an inorganic underlayer made of an inorganic material, a surface modification layer containing an inorganic oxide such as SiO2, an adhesion layer containing a binder such as an acrylic resin laminated on the surface modification layer, and a low refractive index phase in which hollow silica particles are bound by the binder. Patent Document 3 describes a method for producing an optical thin film in which a mixed liquid, prepared by mixing a sol liquid in which magnesium fluoride (MgF2) particles are dispersed and an amorphous silicon oxide-based binder solution, is applied to a substrate and heat-treated, thereby forming a bond between the substrate and the MgF2 particles with the amorphous silicon oxide-based binder and forming a plurality of voids between the MgF2 particles. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2010-38948 A [Patent Document 2] JP 2015-222450 A [Patent Document 3] International Publication No. 2006 / 030848 Summary of the Invention [Problem to be solved by the invention]

[0005] When forming an anti-reflection film or an optical thin film by a sol-gel method, foreign matter may easily get mixed into the film. If the film is mixed with foreign matter or has defects, the foreign matter or defects may absorb light, and the light transmittance of the optical member on which the anti-reflection film or optical thin film is formed may decrease. Even if the light transmittance does not decrease, there are cases where it is better for the surface of the formed antireflection film or optical thin film to be free of metal that was deposited during film formation. An object of one aspect of the present invention is to provide a method for producing an optical thin film and an optical member capable of reducing the presence of metal on the surface of the thin film. [Means for solving the problem]

[0006] The first aspect is a method for producing an optical thin film, comprising the steps of depositing a thin film-forming material on a substrate by vapor deposition in a non-oxidizing atmosphere to form a vapor-deposited film, contacting the vapor-deposited film with a first acidic solution that contains an acidic substance and has a pH range of 2.5 to 3.5 to obtain a thin film having voids, and contacting the obtained thin film with a second acidic solution that contains an acidic substance and has a pH of 2.0 or less while applying ultrasonic vibrations to the second acidic solution, thereby dissolving metal adhering to the surface of the thin film.

[0007] A second aspect is an optical component comprising: an optical thin film that contains indium oxide and silicon oxide and has a refractive index of 1.38 or less; and an object to be deposited, wherein the optical thin film has a plurality of columnar structures continuing from a surface of the object to be deposited to a surface of the optical thin film, and gaps between the columns of the columnar structures; and when the optical thin film is irradiated with light having an illuminance of the reflected light in the range of 1150 lx or more and 1250 lx or less and observed visually, no bright spots due to metal reflection are present on the surface of the optical thin film. Effect of the Invention

[0008] An object of one aspect of the present invention is to provide a method for producing an optical thin film and an optical member capable of reducing the presence of metal on the surface of the thin film. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a flow chart according to a first embodiment of the method for producing an optical thin film. [Diagram 2] FIG. 2 is a photograph showing a thin film in which the presence of bright spots was confirmed. [Diagram 3] FIG. 3 is an enlarged photograph of a portion of FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, an embodiment of the method for producing an optical thin film and an optical member according to the present disclosure will be described. However, the embodiment shown below is an example for embodying the technical idea of ​​the present invention, and the present invention is not limited to the method for producing an optical thin film and the optical member shown below.

[0011] A method for producing a thin film according to one embodiment includes the steps of depositing a thin film-forming material on a substrate by vapor deposition in a non-oxidizing atmosphere to form a vapor-deposited film, contacting the vapor-deposited film with a first acidic solution containing an acidic substance and having a pH in the range of 2.5 to 3.5 to obtain a thin film having voids, and contacting the obtained thin film with a second acidic solution containing an acidic substance and having a pH of 2.0 or higher while applying ultrasonic vibrations to the second acidic solution to dissolve metal adhering to the surface of the thin film.

[0012] The method for producing an optical thin film will be described below with reference to the drawings. Fig. 1 is a flow chart of a first embodiment of the method for producing an optical thin film. The method for producing an optical thin film includes a step S101 of forming a vapor-deposited film, a step S102 of contacting the vapor-deposited film with a first acidic solution to obtain a thin film having voids, and a step S103 of contacting the thin film with a second acidic solution while applying ultrasonic vibrations to dissolve metal attached to the surface of the thin film.

[0013] The thin film forming material preferably contains indium oxide and silicon oxide. By using the thin film forming material containing indium oxide and silicon oxide, a vapor deposition film containing indium oxide (I) (In2O) and silicon dioxide (SiO2) can be formed by physical vapor deposition.

[0014] Indium oxide used as a raw material for the thin film forming material is preferably indium oxide (III) (In2O3). Indium oxide (III) (In2O3) may contain unavoidable impurities. The content of indium oxide (III) (In2O3) in the indium oxide (III) (In2O3) used as a raw material is preferably 90 mass% or more, more preferably 95 mass% or more, and even more preferably 99 mass% or more.

[0015] The silicon oxide used as the raw material of the thin film forming material is preferably silicon monoxide (SiO) as the main component. In this specification, "mainly silicon monoxide (SiO)" means that the content of silicon monoxide (SiO) in the raw material silicon oxide is 50 mass% or more. The content of silicon monoxide (SiO) in the raw material silicon oxide is more preferably 80 mass% or more, even more preferably 90 mass% or more, and even more preferably 99 mass% or more.

[0016] The obtained deposition film may contain a trace amount of indium oxide (III) (In2O3) and / or indium (In). Indium oxide (III) (In2O3) contained in the thin film forming material is dissociated into indium oxide (I) (In2O), indium (In), and oxygen (O) by heating. Silicon monoxide (SiO) contained in the thin film forming material preferentially reacts with oxygen (O) to generate silicon dioxide (SiO2) because the standard free energy of formation of silicon monoxide (SiO) is lower than the standard free energy of formation of indium oxide (I) (In2O). Even when a deposition film is formed using the thin film forming material in a non-oxidizing atmosphere, oxygen (O) dissociated from indium oxide (III) (In2O3) is preferentially absorbed by silicon monoxide (SiO) to generate silicon dioxide (SiO2). Therefore, almost no silicon monoxide (SiO) remains in the deposition film. The thin film (optical thin film) obtained by contacting the evaporated film with an acidic solution does not absorb visible light originating from silicon monoxide (SiO), which has a black body color. In addition, oxygen (O) dissociated from indium oxide (III) (In2O3) contained in the thin film forming material is absorbed by silicon monoxide (SiO) to generate silicon dioxide (SiO2), so the generation of indium oxide (III) (In2O3) due to further oxidation of dissociated indium oxide (I) (In2O) can be suppressed. Indium oxide (I) (In2O) has a very high solubility in acidic substances, so that by contacting the evaporated film with an acidic solution containing an acidic substance, indium oxide (I) (In2O) is preferentially dissolved, and a thin film (optical thin film) having voids that satisfy the desired refractive index and a skeleton composed of silicon dioxide (SiO2) can be obtained.

[0017] The thin film forming material preferably contains indium oxide in the range of 0.230 mol to 0.270 mol per mol of silicon oxide. The thin film forming material more preferably contains indium oxide (III) (In2O3) in the range of 0.240 mol to 0.270 mol per mol of silicon oxide, more preferably contains indium oxide (III) (In2O3) in the range of 0.240 mol to 0.265 mol, even more preferably contains in the range of 0.250 mol to 0.260 mol, and particularly preferably contains in the range of 0.252 mol to 0.258 mol.

[0018] When the molar ratio of indium oxide (III) (In2O3) contained in the thin film forming material is 0.230 or more per mole of silicon oxide, silicon monoxide (SiO) is oxidized to silicon dioxide (SiO2) by oxygen (O) dissociated from indium oxide (III) (In2O3) in the thin film forming material, and the amount of silicon monoxide (SiO) remaining in the deposition film that is not oxidized can be reduced. If silicon monoxide (SiO) remains in the deposition film, silicon monoxide (SiO) does not dissolve even when contacted with the first acidic solution, and silicon monoxide (SiO) with a black body color may cause high absorption of visible light. In addition, if silicon monoxide (SiO) remains in the deposition film, silicon monoxide (SiO) does not dissolve even when contacted with the first acidic solution, and desired voids are not formed, and a thin film having voids that satisfy the desired refractive index may not be obtained. Furthermore, when the molar ratio of indium oxide (III) (In2O3) contained in the thin film forming material is 0.270 moles or less per mole of silicon oxide, it is possible to suppress the generation of an excessive amount of indium oxide (In2O) and / or indium (In) in the vapor-deposited film due to excess indium oxide (III) (In2O3). If the generation of indium oxide (In2O) and / or indium (In) in the vapor-deposited film can be suppressed, it is possible to suppress a decrease in the strength of the obtained thin film due to an excessive number of voids when the vapor-deposited film is contacted with a first acidic solution in a later step to obtain a thin film having voids.

[0019] Indium (In) produced by the dissociation of indium oxide (III) (In2O3) is contained in the atmosphere as indium (In) gas dissociated from indium oxide (III) (In2O3) at a volumetric rate of about 3 to 5% (Thermodynamics of Oxides, by Y. S. Kulikov, Nisso Tsushinsha, p. 146, 1987), and may be present in extremely small amounts in the atmosphere during deposition film formation. The standard free energy of formation of indium (In) oxidized to indium (III) oxide (In2O3) is lower than the standard free energy of formation of silicon monoxide (SiO) oxidized to silicon dioxide (SiO2). When indium (In) dissociated from indium (III) oxide (In2O3) is present in the vapor, the indium (In) in the vapor reacts with oxygen to produce indium (III) oxide (In2O3) again, which may cause the indium (III) oxide (In2O3) to be contained in the vapor-deposited film. When the indium (III) oxide contained in the thin film forming material is within the range of 0.230 mol to 0.270 mol per mol of silicon oxide, the indium (III) oxide (In2O3) reacts with silicon monoxide by oxygen (O) dissociated from indium (III) oxide (In2O3) contained in the thin film forming material, so that the amount of indium (III) oxide (In2O3) and / or indium (In) contained in the vapor-deposited film can be made extremely small. It is preferable that the deposited film does not contain indium (III) oxide (In2O3) and / or indium (In).

[0020] The thin film forming material may contain at least one selected from zirconium oxide and hafnium oxide. The thin film forming material may contain either zirconium oxide or hafnium oxide, or may contain a mixture of both zirconium oxide and hafnium oxide.

[0021] The zirconium oxide used as the raw material for the thin film forming material is preferably zirconium dioxide (ZrO2) as the main component. The content of zirconium dioxide (ZrO2) in the raw material zirconium oxide is more preferably 80 mass% or more, even more preferably 90 mass% or more, and even more preferably 99 mass% or more. The hafnium oxide used as the raw material for the thin film forming material is preferably hafnium dioxide (HfO2) as the main component. The content of hafnium dioxide (HfO2) in the raw material hafnium oxide is more preferably 80 mass% or more, even more preferably 90 mass% or more, and even more preferably 99 mass% or more.

[0022] Zirconium dioxide (ZrO2) or hafnium dioxide (HfO2) has a much lower vapor pressure than indium oxide (III) (In2O3) or silicon monoxide (SiO), and is less likely to disperse, so it tends to accumulate on the evaporation surface of the thin-film forming material. Silicon dioxide (SiO2), which has a relatively higher vapor pressure than the other substances contained in the thin-film-forming material, also accumulates on the evaporation surface of the thin-film-forming material. When electron beam evaporation is selected as the deposition method, silicon dioxide (SiO2) tends to reflect the electron beam. If zirconium dioxide (ZrO2) or hafnium dioxide (HfO2) accumulates on the evaporation surface of the thin-film forming material, the absorption of the electron beam increases, increasing the amount of evaporated silicon dioxide (SiO2), making it easier to form an evaporated film. By adjusting the molar ratio of zirconium dioxide (ZrO2) or hafnium dioxide (HfO2) in the thin film forming material, the amount of silicon dioxide evaporated can be adjusted, and a thin film with any refractive index, from a relatively low refractive index to a slightly high refractive index, can be easily formed. Zirconium dioxide (ZrO2) or hafnium dioxide (HfO2) has a very low vapor pressure compared to indium(III) oxide (In2O3) or silicon monoxide (SiO), so all of it remains in the material and is not included in the thin film.

[0023] When the thin film forming material contains zirconium oxide, the thin film forming material may contain zirconium oxide in a molar ratio of 0.0010 to 0.15, 0.0025 to 0.14, 0.0050 to 0.12, or 0.0100 to 0.12 per mole of indium oxide and silicon oxide in order to adjust the refractive index of the resulting thin film. When the thin film forming material contains hafnium oxide, the thin film forming material may contain hafnium oxide in a molar ratio of 0.0006 to 0.09, 0.0010 to 0.07, 0.0020 to 0.06, or 0.012 to 0.06 per mole of indium oxide and silicon oxide in order to adjust the refractive index of the resulting thin film.

[0024] The thin film forming material includes indium oxide and silicon oxide, and may include at least one selected from zirconium oxide and hafnium oxide as necessary. The raw materials are mixed to form a raw material mixture, and the raw material mixture is molded to form a molded body, which is then fired to form a sintered body. The thin film forming material, which is a sintered body, is vaporized approximately uniformly, and a vapor deposition film can be deposited approximately uniformly on the surface of the film-forming object. The raw material mixture may be molded by press molding. The molded body is preferably fired in an inert atmosphere to prevent excess oxide from being included in the thin film forming material. In this specification, the inert atmosphere refers to an atmosphere mainly composed of argon (Ar) and helium (He). The inert atmosphere may contain oxygen, and when oxygen is contained, the inert atmosphere refers to an oxygen concentration of 15% by volume or less. The concentration of oxygen in the inert atmosphere may be 10% by volume or less, 5% by volume or less, 1% by volume or less, 0.1% by volume or less, 0.01% by volume or less, or 0.001% by volume (10 ppm by volume) or less. The temperature at which the raw material mixture or the molded body is fired may be 500°C or more and 900°C or less, 600°C or more and 880°C or less, or 700°C or more and 850°C or less. If the firing temperature is 500°C or more and 900°C or less, the reaction of the raw materials in the raw material mixture or the molded body is suppressed and the raw materials are vaporized approximately uniformly, so that a sintered body with suppressed cracking and chipping can be obtained.

[0025] The method for producing an optical thin film includes a step of depositing a thin film material on a film-forming object by a vapor deposition method in a non-oxidizing atmosphere to form a vapor-deposited film.

[0026] Examples of the deposition method include physical deposition methods such as electron beam deposition, resistance heating deposition, ion plating, and sputtering. It is preferable to use electron beam deposition or resistance heating deposition, and it is more preferable to use electron beam deposition. Electron beam deposition or resistance heating deposition can form a uniform deposition film even on a curved surface with a large area or a small radius of curvature. Furthermore, the electron beam deposition method has good thermal efficiency because it directly irradiates the thin film forming material with an electron beam to heat it, and even a thin film forming material such as an oxide with a high melting point and low thermal conductivity can be efficiently vaporized, and a deposition film having a stable composition based on the composition of the thin film forming material can be formed on the film formation object in a relatively short time. Furthermore, the deposition film may be formed using ion assist, or ion-beam assisted deposition (IAD) may be used. The ion source for ion beam assist is preferably an inert gas ion, and the inert gas ion can be Ar ion or He ion.

[0027] Since silicon monoxide (SiO) contained in the thin film forming material is a black oxide, if the evaporated film is formed in a non-oxidizing atmosphere, the evaporated film will contain black silicon monoxide (SiO), and the thin film using this evaporated film may not be usable as an optical thin film. Nevertheless, the reason for forming the evaporated film in a non-oxidizing atmosphere is that silicon monoxide (SiO) is preferentially reacted with oxygen to generate silicon dioxide (SiO2), and the generation of indium oxide (III) (In2O3), which has low solubility in acidic solutions, can be suppressed.

[0028] The non-oxidizing atmosphere includes an inert atmosphere, a reducing atmosphere, and a vacuum, and may be one or more of these. An inert atmosphere is an inert atmosphere in which the concentration of oxygen contained in the atmosphere is 15% by volume or less, similar to the inert atmosphere in which a molded product obtained by pressing a raw material mixture is sintered. A reducing atmosphere is an atmosphere in which the main component is a mixed gas containing hydrogen, carbon monoxide, etc. A vacuum is an atmosphere in which the pressure is 1.0×10 -5 Pa or more 1.0×10 -2In this specification, a vacuum refers to an atmosphere in which the pressure is 1.0×10 Pa or less without introducing inert gases such as argon (Ar) gas or helium (He) gas, which are the main components of the inert atmosphere, or mixed gases containing hydrogen, carbon monoxide, etc., into the atmosphere. -5 Pa or more 1.0×10 -2 Pa or less and the oxygen concentration is 15% by volume or less. When the non-oxidizing atmosphere is a vacuum, most of the gas components in the atmosphere are water vapor. When the non-oxidizing atmosphere during deposition film formation is a reducing atmosphere or vacuum in which a mixed gas containing hydrogen and carbon monoxide is introduced, the molar ratio of indium oxide (In2O3 / SiO) to silicon oxide becomes relatively high, and even if the amount of oxygen in the vapor generated from the thin film forming material increases, the hydrogen or carbon monoxide contained in the mixed gas in the atmosphere, or the hydrogen contained in the vacuum, is oxidized faster than the indium oxide (I) (In2O) generated from the thin film forming material, and the generation of indium oxide (III) (In2O3) in the deposition film can be suppressed. When the oxygen concentration in the non-oxidizing atmosphere during deposition film formation is low, the amount of oxygen in the atmosphere is small, so that the indium oxide (I) (In2O) generated from the thin film forming material can be suppressed from being re-oxidized by oxygen in the atmosphere, and the generation of indium oxide (III) in the deposition film can be suppressed. The pressure of the non-oxidizing atmosphere during deposition film formation varies depending on the type of deposition method used. When using electron beam evaporation as the evaporation method, the atmospheric pressure when forming the evaporated film on the film-forming object is 1.0×10 -5 Pa or more 5.0×10 -2 Pa or less, 1.0×10 -5 Pa or more 1.0×10 -2 Pa or less is acceptable, 5.0×10 -5 Pa or more 1.0×10 -2The atmospheric pressure during deposition of the vapor-deposited film may be in the above range, which can prevent indium oxide (I) (In2O) generated from the thin film-forming material from being re-oxidized by oxygen in the atmosphere, and can prevent indium oxide (III) (In2O3) from being generated in the vapor-deposited film. The pressure of the non-oxidizing atmosphere during deposition of the vapor-deposited film can be controlled, for example, by introducing an inert gas such as argon or a mixed gas into the vapor deposition apparatus.

[0029] The object on which the vapor-deposited film is formed may be made of glass or plastic. Examples of glass include optical glass. Examples of plastic include polyester, acrylic, polycarbonate, polyamide, polyimide, polyethersulfone, polysulfone, and polyolefin polymers. The object on which the film is formed may be, for example, a flat or curved lens-shaped substrate, or a flexible sheet.

[0030] The method for producing an optical thin film includes a step of contacting the deposited film with a first acidic solution containing an acidic substance and having a pH range of 2.5 to 3.5 to obtain a thin film having voids. In the method for producing an optical thin film, the deposited film is first contacted with the first acidic solution having a pH range of 2.5 to 3.5 in order to form voids without destroying the skeleton of silicon dioxide (SiO2) by contacting the deposited film with an acid weaker than the second acidic solution described below. If the deposited film is contacted with a strong acid such as the second acidic solution having a pH of 2.0 or less described below without contacting the deposited film with the first acidic solution, the indium oxide (I) (In2O) and / or indium (In) contained in the deposited film will be dissolved from the deposited film too quickly, and part of the silicon dioxide (SiO2) that forms the skeleton will also be easily dissolved, making it difficult to obtain a thin film having voids with silicon dioxide (SiO2) as the skeleton.

[0031] The vapor-deposited film contains indium oxide (I) (In2O) and silicon dioxide (SiO2). The vapor-deposited film may contain a trace amount of indium (In). The indium oxide (I) (In2O) and / or indium (In) contained in the vapor-deposited film have very high solubility in acidic substances. Even if the acidic substance contained in the first acidic solution is a weak acidic substance, the indium oxide (I) (In2O) and / or indium (In) are preferentially dissolved by contacting the vapor-deposited film with the first acidic solution having a pH range of 2.5 to 3.5. By contacting the vapor-deposited film with the first acidic solution, the indium oxide (I) (In2O) and / or indium (In) are preferentially dissolved, and a thin film (optical thin film) having voids with a desired refractive index and a skeleton of silicon dioxide (SiO2) can be obtained.

[0032] Examples of the acidic substance contained in the first acidic solution include inorganic acids such as hydrochloric acid, sulfuric acid, and nitric acid, and organic acids such as acetic acid, citric acid, and oxalic acid. The acidic substance is preferably an acid having a buffering effect and a plurality of acid dissociation constants, and weakly acidic substances such as citric acid and oxalic acid are more preferable. With acids having a small buffering effect, the pH is likely to increase, and therefore a long acid treatment time is likely to be required.

[0033] The pH of the first acidic solution is in the range of pH 2.5 to pH 3.5, preferably in the range of pH 2.7 to pH 3.2. If the pH of the first acidic solution to be contacted with the deposition film is in the range of pH 2.5 to pH 3.5, indium oxide (I) (In2O) and / or indium (In) contained in the deposition film are preferentially eluted at a rate at which the silicon dioxide (SiO2) skeleton in the deposition film is not destroyed, so that the skeleton of silicon dioxide (SiO2) is maintained and a thin film having voids with a desired refractive index can be obtained. Whether the acidic substance contained in the first acidic solution is a strong acidic substance or a weak acidic substance, the first acidic solution is a relatively weak acid as long as the first acidic solution is in the range of pH 2.5 to pH 3.5.

[0034] If the pH of the first acidic solution is below pH 2.5, the acidity is too strong, and the dissolution rate of indium oxide (I) (In2O) and / or indium (In) contained in the vapor deposition film becomes too fast, making it difficult to maintain the skeleton of silicon dioxide (SiO2), and the strength of the thin film may not be obtained. Also, if the pH of the first acidic solution is below pH 2.5, the acidity is too strong, and the adhesion between the obtained thin film and the substrate to be deposited is low, and the thin film may peel off from the substrate to be deposited after contact with the first acidic solution. If the pH of the first acidic solution is above pH 3.5, the dissolution rate of indium oxide (I) (In2O) and / or indium (In) contained in the vapor deposition film becomes slow, and it takes time to completely dissolve indium oxide (In2O) and / or indium (In), which reduces the production efficiency, and is therefore undesirable.

[0035] The temperature at which the vapor-deposited film is brought into contact with the first acidic solution may be room temperature, and the room temperature is in the range of 15°C to 28°C, preferably in the range of 15°C to 25°C. If the temperature at which the vapor-deposited film is brought into contact with the first acidic solution is too high, the solvent of the first acidic solution evaporates, the pH decreases, and the pH of the first acidic solution falls below pH 2.5, which is not preferable. If the temperature at which the vapor-deposited film is brought into contact with the first acidic solution is below or above room temperature of 15°C to 28°C, equipment such as a cooling device for constantly monitoring and adjusting the pH is required to maintain the pH of the first acidic solution in the range of pH 2.5 to pH 3.5, which may increase the production cost.

[0036] The time for which the vapor-deposited film is contacted with the first acidic solution may be any time that the entire thin film becomes transparent when the temperature is room temperature of 15° C. to 28° C., and varies depending on the thickness and size of the vapor-deposited film. When the contact temperature is room temperature of 15° C. to 28° C., the time for which the vapor-deposited film is contacted with the first acidic solution is, for example, preferably 30 minutes or more, may be 40 minutes or more, may be 60 minutes or more, may be 120 minutes or less, or may be 100 minutes or less.

[0037] The method of contacting the evaporated film with the first acidic solution includes a method of immersing the object on which the evaporated film is formed in the first acidic solution, and a method of immersing only the evaporated film formed on the object in the first acidic solution. The object on which the evaporated film is formed may be held in a holder, and the holder holding the object on which the evaporated film is formed may be immersed in the first acidic solution.

[0038] Even if a film having a different composition from the deposited film is laminated on the deposited film to form a multilayer film, the acidic substance contained in the first acidic solution is a weak acidic substance, so that indium oxide (I) (In2O) and / or indium (In) in the deposited film can be eluted without affecting the film having the different composition. Even if a film having a different composition from the deposited film is formed, a silicon dioxide (SiO2) skeleton can be formed by contacting the deposited film and the film having the different composition with the first acidic solution, and a thin film (optical thin film) having a desired porosity can be obtained. The composition of the film laminated on the deposited film can be, for example, a composition containing aluminum oxide.

[0039] In a method for producing an optical thin film, the process of depositing a thin film-forming material on a substrate by a vapor deposition method in a non-oxidizing atmosphere to form a vapor-deposited film, and the process of contacting the vapor-deposited film with a first acidic solution containing an acidic substance and having a pH in the range of 2.5 to 3.5 to obtain a thin film having voids can be described by reference to JP 2020-50945 A.

[0040] The method for producing an optical thin film includes a step of contacting the obtained thin film with a second acidic solution containing an acidic substance and having a pH of 2.0 or less while applying ultrasonic vibrations to the thin film, thereby dissolving metal adhering to the surface of the thin film.

[0041] The second acidic solution to be brought into contact with the obtained thin film has a pH of 2.0 or less, may be 1.5 or less, may be 1.0 or less, or may be -1.14 or more. When the deposited film contains indium oxide (I) (In2O) and / or indium (In), and the deposited film is brought into contact with the first acidic solution having a pH of 2.5 or more and a pH of 3.5 or less, the indium oxide (In2O) and / or indium (In) in the deposited film is dissolved, and a thin film containing voids and a silicon dioxide (SiO2) skeleton is obtained. The dissolved indium oxide (I) (In2O) and / or indium (In) may not be dissolved in the first acidic solution, but may become tiny metal (In) lumps and adhere to the surface of the thin film. The obtained thin film can be brought into contact with a second acidic solution having a pH of 2.0 or less while applying ultrasonic vibration, thereby dissolving the metal (e.g., indium (In)) attached to the surface of the thin film, and a thin film in which no metal is present on the surface or the presence of metal can be reduced can be obtained. The thin film obtained by contacting the vapor-deposited film with the first acidic solution is obtained by contacting the vapor-deposited film with the first acidic solution, which is a relatively weak acid having a pH range of 2.5 to 3.5, and dissolving indium oxide (I) (In2O) and / or indium (In) contained in the vapor-deposited film at a dissolution rate that does not destroy the silicon dioxide (SiO2), thereby obtaining a thin film containing voids and a silicon dioxide (SiO2) skeleton.Therefore, even if the thin film after contacting with the first acidic solution is contacted with a strongly acidic second acidic solution having a pH of 2.0 or less, the silicon dioxide (SiO2) skeleton will not be destroyed, and the metal attached to the surface of the thin film can be dissolved by the second acidic solution.

[0042] When indium oxide (III) (In2O3) is present in the evaporated film and the film is brought into contact with a first acidic solution to obtain a thin film having a silicon dioxide (SiO2) skeleton and voids, if any indium oxide (III) (In2O3) that has not been dissolved remains in the thin film, the refractive index of the thin film may decrease when the thin film is brought into contact with a strongly acidic solution having a pH of 2.0 or less. However, the amount of indium oxide (III) (In2O3) contained in the evaporated film is so small that the refractive index of the thin film decreases by less than 0.04 after the thin film is brought into contact with a strongly acidic solution of pH 2.0. Even if no indium oxide (III) (In2O3) remains in the thin film or a very small amount of indium oxide (III) (In2O3) remains in the thin film, the metal attached to the surface of the thin film can be dissolved and the presence of metal on the surface of the thin film can be reduced by bringing the thin film into contact with a second acidic solution of pH 2.0 or less while applying ultrasonic vibrations.

[0043] The second acid solution preferably contains at least one selected from the group consisting of nitric acid and aqua regia. The second acid solution contains at least one selected from the group consisting of nitric acid and aqua regia, and can be a strongly acidic solution with a pH of 2.0 or less. The thin film is formed by contacting the deposition film in advance with a first acid solution, which is a relatively weak acid in the range of pH 2.5 to 3.5, in which indium oxide (I) (In2O) and / or indium (In) are preferentially dissolved at a relatively slow rate while suppressing the dissolution of silicon. Therefore, the thin film can be brought into contact with a strongly acidic second acid solution with a pH of 2.0 or less while applying ultrasonic vibrations thereto, without destroying silicon dioxide (SiO2) which is the skeleton of the thin film, and the metal attached to the surface of the thin film can be dissolved.

[0044] The second acidic solution does not contain hydrochloric acid, but contains nitric acid, and the concentration of nitric acid is preferably 10% by mass or more. If the second acidic solution does not contain aqua regia containing hydrochloric acid, but contains nitric acid, and the concentration of nitric acid is 10% by mass or more, it can be used as a second acidic solution with a pH of 2.0 or less. If the second acidic solution does not contain hydrochloric acid, the concentration of nitric acid contained in the second acidic solution is more preferably 15% by mass or more, further preferably 20% by mass or more, and may be 70% by mass or less, and is preferably 65% ​​by mass or less. If the second acidic solution does not contain hydrochloric acid but contains nitric acid, the second acidic solution can be made pH 2.0 or less as long as the concentration of nitric acid contained in the second acidic solution is within the range of 10% by mass or more and 70% by mass or less, and the metal attached to the surface of the thin film can be dissolved, and the metal attached to the surface of the thin film can be eliminated or reduced while maintaining the skeleton of the thin film.

[0045] The second acidic solution contains nitric acid, and the concentration of nitric acid is preferably 2.5% by mass or more. The second acidic solution may contain aqua regia containing hydrochloric acid, and if the second acidic solution contains nitric acid and the concentration of nitric acid is 2.5% by mass or more, it can be used as a second acidic solution with a pH of 2.0 or less. When the second acidic solution contains aqua regia containing hydrochloric acid, the concentration of nitric acid contained in the second acidic solution is more preferably 3.75% by mass or more, more preferably 4% by mass or more, and may be 17.5% by mass or less, and is preferably 16.25% by mass or less. When the second acidic solution contains aqua regia containing hydrochloric acid, the second acidic solution can be made pH 2.0 or less as long as the concentration of nitric acid contained in the second acidic solution is within the range of 2.5% by mass or more and 17.5% by mass or less, and the metal attached to the surface of the thin film can be dissolved, and the metal attached to the surface of the thin film can be eliminated or reduced while maintaining the skeleton of the thin film.

[0046] The temperature of the second acidic solution when the thin film is contacted with the second acidic solution is preferably within the range of 30° C. to 60° C. If the temperature of the second acidic solution when the thin film is contacted with the second acidic solution is within the range of 30° C. to 60° C., dissolution of metals attached to the surface of the thin film is promoted, and the metals attached to the surface of the thin film can be eliminated or reduced while maintaining the skeleton of the thin film. The temperature of the second acidic solution when the thin film is contacted with the second acidic solution may be 35° C. or higher, 40° C. or higher, 45° C. or higher, or 55° C. or lower.

[0047] The second acidic solution is brought into contact with the thin film while applying ultrasonic vibration. When the thin film is brought into contact with the second acidic solution to which ultrasonic vibration has been applied, dissolution of the metal attached to the surface of the thin film is promoted, and the metal attached to the surface of the thin film can be eliminated or reduced while maintaining the skeleton of the thin film. The ultrasonic vibration applied to the second acidic solution preferably has an oscillation frequency in the range of 10 kHz to 160 KHz, and may be in the range of 20 kHz to 150 kHz, 30 kHz to 120 kHz, 35 kHz to 100 kHz, 80 kHz or less, 60 kHz or less, or 50 kHz or less. For example, a method of applying ultrasonic vibration to the second acidic solution includes a method of placing a container containing the second acidic solution in a device that applies ultrasonic vibration and applying ultrasonic vibration to the container. For example, an ultrasonic cleaner is used as the device that applies ultrasonic vibration.

[0048] The time for which the thin film is contacted with the second acidic solution is preferably more than 5 minutes, may be 6 minutes or more, may be 7 minutes or more, preferably 8 minutes or more, preferably 20 minutes or less, may be 18 minutes or less, and preferably 15 minutes or less. If the time for which the thin film is contacted with the second acidic solution is more than 5 minutes and 20 minutes or less, the metal attached to the surface of the thin film can be dissolved while maintaining the skeleton of the thin film, and the metal attached to the surface of the thin film can be eliminated or reduced.

[0049] The method of contacting the thin film with the second acidic solution includes a method of immersing the object on which the thin film is formed in the second acidic solution, and a method of immersing only the thin film formed on the object in the second acidic solution. The object on which the thin film is formed may be held in a holder, and the holder holding the object on which the thin film is formed may be immersed in the second acidic solution.

[0050] The method for producing an optical member may include a step of contacting the thin film with a second acidic solution to dissolve metal attached to the surface of the thin film, removing the thin film from the second acidic solution, and drying the thin film. Methods for drying the thin film include natural drying and drying using an air blower.

[0051] An optical member according to an embodiment includes an optical thin film containing indium oxide and silicon oxide and having a refractive index of 1.38 or less, and an object to be coated. The optical thin film has a plurality of columnar structures extending from the surface of the object to the surface of the optical thin film, and gaps between the columns of the columnar structures. When the optical thin film is irradiated with light having an illuminance of reflected light in the range of 1150 lx to 1250 lx and visually confirmed, no bright spots due to metal reflection are present on the surface of the optical thin film. When the optical thin film is irradiated with light having an illuminance of reflected light in the range of 1150 lx to 1250 lx, no bright spots due to metal reflection are present, and no metal is present on the surface of the optical thin film. In this specification, bright spots refer to small spots of light caused by metal reflection. The diameter of the bright spots is in the range of 5 μm to 15 μm, and is generally around 10 μm. When the optical thin film is irradiated with light having an illuminance of reflected light in the range of 1150 lx to 1250 lx, if even one bright spot caused by metal reflection is found by visual inspection, it can be confirmed that metal remains on the surface of the optical thin film. The optical thin film preferably has a thin film obtained by the above-mentioned manufacturing method, in which the metal adhering to the surface of the thin film has been dissolved.

[0052] A method for confirming the presence of bright spots on the surface of the optical thin film includes, for example, using a lighting device capable of irradiating light with an illuminance of reflected light in the range of 1150 lx to 1250 lx, placing an optical member in a range where the light of the lighting device can be irradiated at a distance of about 10 cm to 20 cm from the light source of the lighting device, and visually confirming the surface of the optical thin film of the optical member. The optical thin film of the optical member irradiated with light with an illuminance of reflected light in the range of 1150 lx to 1250 lx may be photographed with a digital camera to confirm the presence of bright spots. When photographing the optical thin film of the optical member with a digital camera, the surface of the optical thin film may be photographed at a position about 5 cm to 15 cm away from the surface of the optical thin film of the optical member. In order to make it easier to confirm the presence of bright spots, a lighting device and an optical member may be placed in a darkroom, and the optical thin film may be irradiated with light with an illuminance of reflected light in the range of 1150 lx to 1250 lx, and the bright spots may be visually confirmed, or the optical thin film of the optical member may be photographed with a digital camera. The lighting fixture may use a fluorescent lamp as a light source, or may use a light-emitting device equipped with a light-emitting element such as a light-emitting diode.

[0053] The thin film that is an optical thin film preferably has a thin film obtained by dissolving metal attached to the surface of the thin film obtained by the above-mentioned manufacturing method. The thin film that is an optical thin film preferably has a columnar structure continuing from the surface of the object to be deposited to the surface of the optical thin film, the columnar structure continuing from the surface of the object to be deposited to the surface of the optical thin film as a skeleton. The thin film that is an optical thin film has a plurality of columnar structures. For example, in a cross-sectional SEM photograph of the optical thin film taken with a scanning electron microscope (SEM), the number of connection points between the columnar structure and the object to be deposited (e.g., the base film) may be 5 or more within a width of 500 nm. Also, in a cross-sectional SEM photograph, the number of connection points between the columnar structure and the object to be deposited may be 20 or less within a width of 500 nm.

[0054] The refractive index of the thin film that is an optical thin film is preferably lower than that of silicon dioxide (SiO2), and is preferably 1.38 or less. Since the thin film that is an optical thin film has a refractive index of 1.38 or less, it can enhance the anti-reflection effect over the entire visible range. The refractive index of the optical thin film can be calculated by measuring the reflection spectrum with a spectrophotometer, measuring the minimum value of the reflected light intensity when the incident light intensity is set to 100%, and using the Fresnel coefficient from this minimum value of the measured reflectance. The refractive index of the thin film that is an optical thin film is preferably 1.25 or less, and more preferably 1.20 or less.

[0055] The thin film that is an optical thin film preferably has a porosity in the range of 30% or more and 90% or less. If the porosity of the thin film is 30% or more, the refractive index of the thin film can be reduced, and if it is 90% or less, the refractive index of the thin film can be reduced while maintaining the strength to maintain the thin film formed on the substrate. The porosity of the thin film that is an optical thin film is more preferably in the range of 40% or more and 90% or less, even more preferably in the range of 50% or more and 90% or less, and even more preferably in the range of 60% or more and 85% or less. The porosity (total porosity Vp) of the thin film that is an optical thin film can be calculated using the Lorentz-Lorenz equation based on the examples described later.

[0056] An optical member comprising an optical thin film and a film-forming object can be used in optical members such as astronomical telescopes, eyeglass lenses, cameras, disc drive devices equipped with optical pickup parts such as bandpass filters and beam splitters, and display devices equipped with high-definition liquid crystal panels. In addition, by applying the optical thin film to a portion of a light-emitting device that extracts light to the outside, it is possible to promote the emission of light from the light-emitting device to the outside, and to expect an improvement in the light extraction efficiency and a reduction in heat generation.

[0057] The present disclosure may include the following aspects. [Section 1] A step of depositing a thin film forming material on a film-forming object by a deposition method in a non-oxidizing atmosphere to form a deposited film; contacting the deposited film with a first acidic solution containing an acidic substance and having a pH in the range of 2.5 to 3.5 to obtain a thin film having voids; and contacting the obtained thin film with a second acidic solution containing an acidic substance and having a pH of 2.0 or less while applying ultrasonic vibrations to the thin film, thereby dissolving metal adhering to the surface of the thin film. [Section 2] Item 2. The method for producing an optical thin film according to item 1, wherein the thin film forming material contains indium oxide and silicon oxide. [Section 3] Item 3. The method for producing an optical thin film according to item 1 or 2, wherein the second acid solution contains at least one selected from the group consisting of nitric acid and aqua regia. [Section 4] 3. The method for producing an optical thin film according to item 1 or 2, wherein the second acidic solution does not contain hydrochloric acid but contains nitric acid, and the concentration of the nitric acid is 10 mass % or more. [Section 5] Item 5. The method for producing an optical thin film according to item 1, 2 or 4, wherein the second acidic solution contains nitric acid and has a concentration of 2.5 mass % or more. [Section 6] 6. The method for producing an optical thin film according to claim 1, 2, 4 or 5, wherein the temperature of the second acidic solution when the thin film is brought into contact with the second acidic solution is within a range of 30° C. or more and 60° C. or less. [Section 7] Item 7. The method for producing an optical thin film according to any one of items 1 to 6, wherein the thin film is contacted with the second acidic solution for more than 5 minutes. [Section 8] The optical thin film includes indium oxide and silicon oxide and has a refractive index of 1.38 or less, and an object to be coated; the optical thin film has a plurality of columnar structures extending from a surface of the deposition target to a surface of the optical thin film, and gaps between columns of the columnar structures, An optical component in which, when the optical thin film is irradiated with light having an illuminance of reflected light in the range of 1150 lx to 1250 lx and the optical thin film is visually observed, no bright spots due to metal reflection are present on the surface of the optical thin film. [Section 9] Item 9. The optical member according to item 8, wherein the optical thin film has a porosity in the range of 30% to 90%. EXAMPLES

[0058] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0059] Example 1 Manufacturing of thin film forming materials 160g of indium oxide (III) powder (In2O3) (purity: 99.99% by mass), 100g of silicon monoxide powder (SiO) (purity: 99.9% by mass), and 13.0g of zirconium dioxide (ZrO2) (purity: 99.9% by mass) were placed in a 1L nylon pot, and a nylon ball with a diameter of 20 mm (φ20) was placed together with these powders. The mixture was mixed for 30 minutes while breaking up the agglomerates to obtain a raw material mixture. The molar ratio of indium oxide to 1 mole of silicon oxide (In2O3 / SiO molar ratio) was 0.254, and the molar ratio of zirconium oxide to the total of 1 mole of indium oxide and silicon oxide (ZrO2 / In2O3 and SiO total) was 0.022. The raw material mixture was removed from the pot and pressed into a molded body. This compact was sintered in an inert atmosphere (argon (Ar): 99.99% by volume) at 800° C. for 2 hours to obtain a thin film forming material (sintered body).

[0060] Production of evaporated films A disk-shaped double-sided polished glass (manufactured by SCHOOT AG, BK=7) with a diameter of 30 mm was used as the film-forming object. The film-forming object and the thin film-forming material were placed in the deposition apparatus, and the pressure in the deposition apparatus was increased to 2.0×10 -4With the pressure reduced to 10 Pa, the thin film forming material was irradiated with an electron beam (JEBG-102UHO, manufactured by JEOL Ltd.) at 90 mA to form a deposition film containing indium oxide (I) (In2O) and silicon dioxide (SiO2) on one side of the substrate-like film-forming object. The temperature of the film-forming object during film formation was set to 100°C, and ion-beam assisted deposition (IAD) (acceleration voltage value-acceleration current value 800V-800mA) was used using Ar ions emitted from an ion gun (NIS-150, manufactured by Shincron Co., Ltd.). A neutralizer (RFN-2, manufactured by Shincron Co., Ltd., bias current value 1000mA) was also used to prevent charging up of the film-forming object.

[0061] Fabrication of porous thin films An oxalic acid solution with a pH of 3.2 was prepared as the first acidic solution. The object on which the deposition film was formed was immersed in the first acidic solution at room temperature (20°C to 25°C) to bring the deposition film into contact with the first acidic solution. Indium oxide (I) (In2O) was preferentially eluted from the deposition film that had been brought into contact with the first acidic solution to produce a thin film having voids. The contact time (immersion time) between the deposition film and the first acidic solution was 90 minutes, and a thin film with low absorption of visible light was obtained. The refractive index of the thin film having voids obtained was measured by the method described below. A thin film having voids with a refractive index of 1.182 was obtained. The porosity of the thin film was 68%.

[0062] Dissolution of metals attached to the surface of thin films The thin film thus obtained was irradiated with light having an illuminance of reflected light in the range of 1150 lx to 1250 lx, and it was confirmed that bright spots were present and that the metal In was attached to the surface of the thin film thus obtained. A second acid solution having a pH of -0.66 at room temperature (20°C to 25°C) was prepared in an amount that allowed the film-forming object with a thin film to be immersed. The second acid solution was a nitric acid solution containing no hydrochloric acid and having a nitric acid concentration of 25 mass% relative to the total amount of the second acid solution. The film-forming object with a thin film formed thereon was immersed in the second acid solution to bring the thin film into contact with the second acid solution. The temperature of the second acid solution when it was brought into contact with the thin film was set to 50°C. The contact time (immersion time) between the thin film and the second acid solution was set to 10 minutes. The second acid solution in which the film-forming object with a thin film formed thereon was immersed was placed in an ultrasonic cleaner (HFC-3D, manufactured by AS ONE Corporation) together with the container containing the second acid solution. The second acid solution was brought into contact with the thin film while ultrasonic vibrations with an oscillation frequency of 40 kHz were applied. After the thin film was contacted with the second acidic solution, the thin film-containing object was removed from the second acidic solution, and the surface of the thin film was dried by air blowing to obtain a thin film after contact with the second acidic solution. The thin films of the examples and comparative examples were visually inspected for the presence of bright spots on the surface of the thin film after contact with the second acidic solution by the method described below.

[0063] Examples 2 to 6 In the process of dissolving metal adhering to the surface of the thin film, the thin film was contacted with the second acidic solution in the same manner as in Example 1, except that the concentration of nitric acid in the second acidic solution was set to the concentrations shown in Table 2, and a thin film after contact with the second acidic solution was obtained.

[0064] Examples 7 to 10 In the process of dissolving metal adhering to the surface of the thin film, the thin film was contacted with the second acidic solution in the same manner as in Example 1, except that the time for which the thin film was contacted with the second acidic solution was set to the time shown in Table 2, and a thin film after contact with the second acidic solution was obtained.

[0065] Example 11 In the process of dissolving metal adhering to the surface of the thin film, the thin film was brought into contact with the second acidic solution in the same manner as in Example 1, except that the temperature of the second acidic solution when contacting the thin film with the second acidic solution was room temperature (20°C to 25°C) and the second acidic solution was not heated, and the thin film after contact with the second acidic solution was obtained.

[0066] Reference example 1 A thin film was obtained in the same manner as in Example 1, except that the step of dissolving the metal adhering to the surface of the thin film was not carried out.

[0067] Reference example 2 In the process of dissolving metal adhering to the surface of the thin film, the thin film was brought into contact with the second acidic solution in the same manner as in Example 1, except that ultrasonic vibration was not applied to the second acidic solution when the thin film was brought into contact with the second acidic solution, and a thin film after contact with the second acidic solution was obtained.

[0068] The refractive index of the thin film was measured before and after contact with the second acidic solution used in Examples 1 and 4 and Reference Example 1. As described above, the refractive index of the thin film before contact with the second acidic solution was 1.182. The refractive indexes of the thin films after contact with the second acidic solution in Examples 1 and 4 and Reference Example 1 are shown in Tables 1 and 2.

[0069] How to measure the refractive index A spectrophotometer (U-4100, Hitachi High-Technologies Corporation, incident angle 5°) was used to measure the reflection spectrum of each thin film (optical thin film) of Examples 1, 4, and Reference Example 1. The minimum value of the reflected light intensity when the incident light intensity was taken as 100 was measured as the reflectance, and the refractive index was calculated from this measured reflectance using the Fresnel coefficient. In Examples 1 and 4 and Reference Example 1, double-sided polished glass was used as the substrate on which the thin film was formed, so the reflectance R' obtained from the measurement included multiple repeated reflections including backside reflection. Since the measured reflectance R' includes multiple repeated reflections, the reflectance R of the thin film can be expressed by the following formula (1).

[0070]

number

[0071] In the formula (1), R ois the reflectance of the substrate (the object on which the film is formed). In the method for measuring the refractive index, the object on which the film is formed is also called the substrate. The reflectance R of the base film or thin film was calculated based on the reflectance R' of the base film or thin film that was actually measured, according to formula (1). The reflectance R of the base film or thin film is the reflectance that does not take into account the reflection from the back surface. The reflectance R of the undercoat or thin film is expressed as the Fresnel coefficient: m and the refractive index n of the undercoat film or thin film can be expressed by the following formula (2).

[0072]

number

[0073] Here, the refractive index of the air is approximated as 1, and the refractive index of the substrate is n m When the refractive index n of the undercoat film or thin film is larger than the square root of the refractive index n of the undercoat film or thin film, the refractive index n of the undercoat film or thin film can be expressed by the following formula (3).

[0074]

number

[0075] In addition, the refractive index of the substrate, n m When the refractive index n of the undercoat film or thin film is smaller than the square root of the refractive index n of the undercoat film or thin film, the refractive index n of the undercoat film or thin film can be expressed by the following formula (4).

[0076]

number

[0077] The refractive index n of the undercoat film or thin film was calculated based on the above formulas (1) to (4). The refractive index n of the undercoat film or thin film was calculated based on "Kohiyama Mitsunobu, 'Basic Theory of Optical Thin Films - Fresnel Coefficients, Characteristic Matrices', Optronics Co., Ltd., February 25, 2011, Revised and Enlarged Edition, First Printing."

[0078] Porosity (%) The porosity (total porosity Vp) of the thin film was calculated using the Lorentz-Lorenz equation shown in the following formula (5). In the following formula (5), n f is the observed refractive index of the thin film, and n b is the refractive index of the skeleton of the thin film. The refractive index of the thin film, n f is the refractive index of the thin film calculated based on the above formulas (1) to (4). The refractive index of the thin film skeleton, n b Since it is mainly composed of silicon dioxide (SiO2), the refractive index of silicon dioxide (SiO2) (1.460) was used to calculate it.

[0079]

number

[0080] Check for the presence of bright spots on optical components Using a lighting device capable of irradiating light with an illuminance of reflected light in the range of 1150 lx to 1250 lx, an optical member was placed in a range where the light of the lighting device could be irradiated, at a distance of about 10 cm to 20 cm from the light source of the lighting device, and the surface of the optical thin film of the optical member was visually confirmed. In addition, the surface of the optical thin film was photographed with a digital camera at a position about 5 cm to 15 cm away from the surface of the optical thin film of the optical member. When visually confirming or photographing with a digital camera, light with an illuminance of reflected light in the range of 1150 lx to 1250 lx was irradiated onto the surface of the thin film of the optical member in a dark room. In Example 1, 100 thin films (optical thin films) were obtained after contacting with the second acid solution in the same manner, and the number of thin films out of the 100 that did not have a bright spot on the surface of the thin film was confirmed, and the number of thin films out of the 100 that did not have a bright spot was expressed as a yield (%). The results are shown in Table 1. In Examples 2 to 11 and Reference Examples 1 and 2, ten thin films (optical thin films) were obtained after contacting with the second acidic solution in the same manner in one Example or Reference Example, and the number of thin films among the ten that did not have bright spots on the surface was counted, and the number of thin films that did not have bright spots per ten was expressed as the yield (%). The results are shown in Table 2.

[0081] [Table 1]

[0082] [Table 2]

[0083] The thin films (optical thin films) of Examples 1 to 11 were obtained with a yield of 70% or more (yield of 70 or more out of 100 or 7 or more out of 10) by contacting them with a second acidic solution having a pH of 2.0 or less, and were free of bright spots caused by In, a metal, adhering to the surface of the thin film. Furthermore, the thin films (optical thin films) according to Examples 1 and 4 showed a decrease in refractive index of less than 0.04 before and after contact with the second acidic solution having a pH of 2.0 or less. It was confirmed that the thin films (optical thin films) according to Examples 1 and 4 before contact with the second acidic solution did not contain indium oxide (III) (In2O3), or even if they contained indium oxide (III) (In2O3), the amount was less than the amount that would cause a decrease in refractive index of 0.04.

[0084] The thin film (optical thin film) according to Reference Example 1 was not subjected to a step of dissolving the metal adhering to the surface of the thin film. In Reference Example 1, the yield of thin films without bright spots caused by In, which is a metal adhering to the surface of the thin film, was 0 out of 10 (0% yield). As in Examples 1 to 11, it was confirmed that the yield was significantly improved by performing a step of dissolving the metal adhering to the surface of the thin film.

[0085] In Reference Example 2, the yield of thin films free of bright spots caused by In, a metal adhering to the surface of the thin film, was 7 out of 10 (70% yield), which was lower than that of Example 1. It was confirmed that the yield could be improved not only by contacting with the second acidic solution having a pH of 2.0 or less as in Example 1, but also by applying ultrasonic vibration to the second acidic solution.

[0086] The results of Examples 4 and 7 to 10 show that the yield of thin films free of bright spots caused by In, a metal that adheres to the surface of the thin film, changes depending on the contact time between the thin film and the second acidic solution.

[0087] From the results of Examples 4 and 11, it was confirmed that by increasing the temperature of the second acidic solution when the thin film is brought into contact with the second acidic solution above room temperature (20°C to 25°C), the yield of a thin film that does not have bright spots caused by In, a metal that adheres to the surface of the thin film, is improved.

[0088] Fig. 2 is a photograph showing the thin film 1 in which the presence of bright spots 2 was confirmed. Fig. 3 is a photograph showing an enlarged portion of Fig. 2. When light with an illuminance of reflected light in the range of 1150 lx to 1250 lx was irradiated in a dark room, white bright spots due to reflection of the metal In were confirmed on the surface of the thin film 1 in the photographs shown in Fig. 2 and Fig. 3. The diameter of the bright spots was approximately 10 μm. [Industrial Applicability]

[0089] According to the method for producing a thin film according to one embodiment, an optical thin film with reduced metal presence on the surface of the thin film can be produced, and an optical thin film that can be used not only for camera lenses but also for high-definition liquid crystal panels, etc. The optical member according to one embodiment can be used as an optical member for astronomical telescopes, eyeglass lenses, cameras, disc drive devices equipped with optical pickup parts such as bandpass filters and beam splitters, display devices equipped with high-definition liquid crystal panels, etc. [Explanation of symbols]

[0090] 1: thin film, 2: bright spot.

Claims

1. A step of depositing a thin film forming material on a film-forming object by a deposition method in a non-oxidizing atmosphere to form a deposited film; contacting the deposited film with a first acidic solution containing an acidic substance and having a pH in the range of 2.5 to 3.5 to obtain a thin film having voids; and contacting the obtained thin film with a second acidic solution containing an acidic substance and having a pH of 2.0 or less while applying ultrasonic vibrations to the thin film, thereby dissolving metal adhering to the surface of the thin film.

2. The method for producing an optical thin film according to claim 1 , wherein the thin film forming material contains indium oxide and silicon oxide.

3. The method for producing an optical thin film according to claim 1 or 2, wherein the second acid solution contains at least one selected from the group consisting of nitric acid and aqua regia.

4. 3. The method for producing an optical thin film according to claim 1, wherein the second acidic solution does not contain hydrochloric acid but contains nitric acid, and the concentration of the nitric acid is 10 mass % or more.

5. The method for producing an optical thin film according to claim 1 , wherein the second acidic solution contains nitric acid, and the concentration of the nitric acid is 2.5 mass % or more.

6. 3. The method for producing an optical thin film according to claim 1, wherein the temperature of the second acidic solution when the thin film is brought into contact with the second acidic solution is within a range of 30°C or more and 60°C or less.

7. The method for producing an optical thin film according to claim 1 or 2, wherein the thin film is contacted with the second acidic solution for a period of time exceeding 5 minutes.

8. The optical thin film includes indium oxide and silicon oxide and has a refractive index of 1.38 or less, and an object to be coated; the optical thin film has a plurality of columnar structures extending from a surface of the deposition target to a surface of the optical thin film, and gaps between columns of the columnar structures, An optical component in which, when the optical thin film is irradiated with light having an illuminance of reflected light in the range of 1150 lx to 1250 lx and the optical thin film is visually observed, no bright spots due to metal reflection are present on the surface of the optical thin film.

9. The optical member according to claim 8 , wherein the optical thin film has a porosity in the range of 30% to 90%.

Citation Information

Patent Citations

  • Antireflection coating, optical member comprising the same, exchange lens and imaging device

    JP2010038948A

  • Anti-reflection film and optical element

    JP2015222450A

  • MgF2 OPTICAL THIN FILM CONTAINING AMORPHOUS SILICON OXIDE BINDER, OPTICAL DEVICE HAVING SAME, AND METHOD FOR PRODUCING SUCH MgF2 OPTICAL THIN FILM

    WO2006030848A1